Developing picture storybooks assisted by word search puzzle to improve elementary students’ indonesian vocabulary mastery - Andhini Pramudita; Nugraheti Sismulyasih SB (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
This study presents the low reading comprehension of elementary students associated with limited vocabulary mastery. It aims to develop picture storybooks assisted by a word search puzzle and examine their feasibility and the tendency of vocabulary improvement after implementation. The study employed a Research and Development (R&D) design based on Borg & Gall’s model, adapted into eight stages. The participants were 30 fourth-grade students of SDN Jatilor Grobogan, including a small-scale trial (6 students) and a usage trial (24 students). Data were collected through observation, interviews, questionnaires, and pre-test–post-test using valid and reliable instruments. Product feasibility was evaluated by a media expert, a material expert, a teacher, and students. Meanwhile, effectiveness testing employed a one-group pre-test–post-test design, and was analyzed using a paired-sample t-test and N-Gain. The results indicated that the product was highly feasible, with scores above 90%. Statistical analysis showed a significant difference between pre-test and post-test scores (p < 0.05), with mean scores increasing from 63.75 to 80.83 and an N-Gain of 47,11% (moderate category). These findings indicate an improvement in vocabulary mastery following implementation, although these should be interpreted with caution due to the absence of a control group.